Role of microRNAs in Stroke and Poststroke Depression - Han Yan; Min Fang; Xue-Yuan Liu (The Scientific World Journal)
microRNAs (miRNA), a sort of noncoding RNAs widely distributed in eukaryotic cells, could regulate gene expression by inhibiting transcription or translation. They were involved in important physiological and pathological processes including growth, development, and occurrence and progression of diseases. miRNAs are crucial for the development of the nervous system. Recent studies have demonstrated that some miRNAs play important roles in the occurrence and development of ischemic cerebrovascular diseases such as stroke and were also involved in the occurrence and development of poststroke depression (PSD). Herein, studies on the role of miRNAs in the cerebral ischemia and PSD were reviewed, and results may be helpful for the diagnosis and prognosis of cerebral ischemia and PSD with miRNAs in clinical practice.